ANALISIS KESULITAN GURU DALAM MENERAPKAN PEMBELAJARAN SAINTIFIK PADA MATAPELAJARAN IPS DI SMP NEGERI KOTA PALEMBANG - Han Shella Ningsih; Dewi Koryati; Deskoni deskoni (Jurnal Profit Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
Abstract: This study attempts to: (1) described the difficulties of teachers in the implementation of scientific learning in social studies (IPS) in Junior High Schools Palembang, and (2) know the efforts in do teachers in overcome difficulties in the implementation of scientific learning in social studies (IPS) in Junior High Schools Palembang. This research is research  of population to technique with drawal sample is sampling area. The Regions select are Ilir Barat I. In Kecamatan Ilir Barat I there are junior high schools 17 and junior high schools 33. Sample in this research was teachers social class junior high schools 17 and teachers social class junior high schools 33 the city of palembang which consisted of 14 people. Technique data collection in use is chief and interview. Test validity using formulas product moment of pearson and reliability test using formulas cronbach’s alpha. Technique analysis the data in use is analysis statistik-deskriptif who later in interpretation into the form of the percentage. The research results show that: (1) teachers in implementing learning rendering on the subjects of social class included in the category quite challenging in activities create or gather information. (2) difficulty in learning activities scientific is in overcome teachers by seeking information / the necessary data through reading books in a library and to find information with discuss fellow other teachers.Abstrak: Penelitian ini bertujuan untuk: (1) mendeskripsikan kesulitan guru dalam pelaksanaan pembelajaran saintifik pada mata pelajaran IPS di SMP Negeri Kota palembang; dan (2) mengetahui upaya yang di lakukan guru dalam mengatasi kesulitan dalam  pembelajaran saintifik pada mata pelajaran IPS di SMP Negeri Kota Palembang. Penelitian ini adalah penelitian populasi dengan teknik penarikan sampel adalah sampling area. Daerah yang di pilih yaitu Kecamatan Ilir barat I. Di kecamatan Ilir barat I terdapat SMP Negeri 17 dan SMP Negeri 33. Sampel dalam penelitian ini adalah guru-guru IPS SMP Negeri 17 dan guru-guru IPS SMP Negeri 33 Kota Palembang yang berjumlah 14 orang. Teknik pengumpulan data yang di gunakan adalah angket dan wawancara. Uji validitas menggunakan rumus Product moment dari Pearson dan uji reliabilitas menggunakan rumus Cronbach’s Alpha. Teknik analisis data yang di gunakan adalah analisis statistik-deskriptif yang kemudian diinterpretasikan ke dalam bentuk persentase. Hasil penelitian menunjukkan bahwa: (1) guru dalam melaksanakan pembelajaran saintifik pada mata pelajaran IPS masuk dalam kategori cukup sulit dalam kegiatan mencipta atau mengumpulkan informasi. (2) kesulitan dalam kegiatan pembelajaran saintifik tersebut di atasi guru dengan mencari informasi/data yang diperlukan melalui membaca buku di perpustakaan dan mencari informasi dengan berdiskusi sesama guru lain.